An Analysis of Brazil’s Economic Situation: 2014-2017, the short-term outlook and policy alternatives - Nassif, André (Brazilian Keynesian Review, 2017)
The main goal of this paper is to discuss Brazil’s economic situation in the recent period. Although the analysis is centred on the current Brazilian business conditions (known as the conjuntura econômica in the Portuguese language), the paper covers the period after 2014, during which the country’s economic problems have significantly worsened. The remainder of the paper is divided into the following sections. Section 2 seeks to analyze and discuss the main structural and short-term causes that explain the worsening of Brazil’s economic situation in 2014, as well as the deep recession that followed it. Section 3 critically analyzes the macroeconomic policy adopted by Temer’s government, assuming implicitly that there are both fiscal and monetary policy alternatives. Section 4 concludes and discusses economic policy alternatives for growth recovery of the Brazilian economy, other than those chosen and adopted by Temer’s economic team in 2016 and onwards.